Potential cost‐effectiveness of wearable cardioverter‐defibrillator for patients with implantable cardioverter‐defibrillator explant in a high‐income city of China - Jiang, Xinchan; Ming, Wai‐Kit; You, Joyce H. S. (Journal of cardiovascular electrophysiology, 2019)
Introduction Wearable cardioverter‐defibrillator (WCD) is recommended for patients with implantable cardioverter‐defibrillator (ICD) removal. This study aimed to investigate the potential cost‐effectiveness of WCD for patients with ICD explant in a high‐income city of China. Methods and Results A 5‐year decision‐analytic model was developed to simulate outcomes of three strategies during the period between ICD explant and reimplantation: discharge‐to‐home without WCD (home group), discharge‐to‐home with WCD (WCD group), and stay‐in‐hospital (hospital group). Outcome measures were mortality rates (during the period between ICD explant and reimplantation), direct medical costs, quality‐adjusted life years (QALYs), and incremental cost per QALY saved (ICER). Model inputs were derived from literature and public data. Base‐case analysis was performed at four cost levels of WCD. Robustness of model results was examined by sensitivity analyses. In base‐case analysis, the 8‐week mortality rates of WCD, hospital, and home groups were 7.3%, 8.1%, and 9.4%, respectively. WCD group gained the highest QALYs (3.0990 QALYs), followed by hospital group (3.0553 QALYs) and home group (3.0132 QALYs). The WCD group was the cost‐effective option with ICERs less than willingness‐to‐pay (WTP) threshold (57 315 USD/QALY) at WCD daily cost ≤USD48. In probabilistic sensitivity analysis, the WCD group at daily cost of USD24, USD48, USD72, and USD96 were cost‐effective in 100%, 94.16%, 22.08%, and 0.16% of 10 000 Monte Carlo simulations, respectively. Conclusions Use of WCD during the period between ICD explant and reimplantation is likely to save life and gain higher QALYs. Cost‐effectiveness of WCD is highly subject to the daily cost of WCD in China.